2005
DOI: 10.1161/circulationaha.105.571653
|View full text |Cite
|
Sign up to set email alerts
|

Mineralocorticoid Receptor Antagonism Ameliorates Left Ventricular Diastolic Dysfunction and Myocardial Fibrosis in Mildly Symptomatic Patients With Idiopathic Dilated Cardiomyopathy

Abstract: Background— Mineralocorticoid receptor antagonism reduces mortality associated with heart failure by mechanisms that remain unclear. The effects of the mineralocorticoid receptor antagonist spironolactone on left ventricular (LV) function and chamber stiffness associated with myocardial fibrosis were investigated in mildly symptomatic patients with idiopathic dilated cardiomyopathy (DCM). Methods and Results— Twe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
150
3
2

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 240 publications
(160 citation statements)
references
References 26 publications
5
150
3
2
Order By: Relevance
“…This HR reduction enhances coronary perfusion and lowers O 2 demand and LV filling pressure. The above-mentioned changes induce LV reverse remodeling in patients with CHF some medications for CHF treatment might alter turnover of extracellular matrix [11,[35][36][37], they might have some influence on collagen metabolism. We think that this factor would have a minimal effect, because almost all of the patients were treated with angiotensin-converting enzyme inhibitors or angiotensin receptor blockers and a multivariate analysis showed that administration of aldosterone antagonist was not selected as a significant factor to explain LV functional recovery in this study.…”
Section: Limitations Of the Studymentioning
confidence: 99%
“…This HR reduction enhances coronary perfusion and lowers O 2 demand and LV filling pressure. The above-mentioned changes induce LV reverse remodeling in patients with CHF some medications for CHF treatment might alter turnover of extracellular matrix [11,[35][36][37], they might have some influence on collagen metabolism. We think that this factor would have a minimal effect, because almost all of the patients were treated with angiotensin-converting enzyme inhibitors or angiotensin receptor blockers and a multivariate analysis showed that administration of aldosterone antagonist was not selected as a significant factor to explain LV functional recovery in this study.…”
Section: Limitations Of the Studymentioning
confidence: 99%
“…More recently, Izawa et al [13] investigated the effects of spironolactone in patients with dilated cardiomyopathy. The patients were divided into two groups on the basis of the serum PIP/CITP ratio (B35, group A, n = 12; [35, group B, n = 13), an index of myocardial collagen accumulation.…”
Section: Aldosterone Antagonistsmentioning
confidence: 99%
“…Thus, the PICP/CITP serum levels ratio serves as a serum marker of myocardial collagen accumulation. In patients with dilated cardiomyopathy, Izawa et al [13] demonstrated that both collagen volume fraction and the abundance of collagen types I and III mRNAs in the LV myocardium were higher in the patients with an increased PICP/CITP serum level ratio than in those with a lower PIP/CITP ratio. This is a direct evidence linking serum ECM markers to the heart ECM content, thus providing rationale for their use as potentially useful biomarkers of ECM remodelling in cardiac disease.…”
Section: Introductionmentioning
confidence: 99%
“…AngII has a direct effect on fibroblasts and increases transforming growth factor (TGF)-b which in turn increases collagen production [26][27][28]. ACE inhibition, ARBs, and aldosterone antagonists reduce collagen production and fibrosis [15,29]. Novel renin inhibitors such as aliskiren show promise in reducing cardiac fibrosis in animal models [30].…”
Section: The Extracellular Matrix In End-stage Heart Failurementioning
confidence: 99%